Study of Aspects of Economic Education and Entrepreneurial Capital in Making Entrepreneurial Decisions of Street Vendors - Anisa Muawanah Azzahra; Muhammad Hasan; Muhammad Dinar; Tuti Supatminingsih; Muhammad Ihsan Said (HUMAN: South Asian Journal of Social Studies, 2021)
Abstract.  This study aims to determine the aspects of economic education and entrepreneurial capital of street vendors in the Barru City square area. This research uses qualitative methods, using data collection techniques with observation, interviews and documentation. With the data collection techniques above, the education aspect of street vendors in the Barru town square is one of the factors that support entrepreneurial success, with the assumption that better education will provide street vendors with knowledge in managing a business. Meanwhile, in terms of entrepreneurial capital, it shows that the distribution of capital by the government is not completely evenly distributed to traders in the square area and this capital is very important to support the smooth running of the street vendors. Keywords: Economic Education, Entrepreneurial Capital, Street Vendors